English Language Teachers' Perceptions of their Professional Needs in the Malaysian Context - Khandehroo, Koroush (2010)
Professional Development, in a broad sense, refers to the development of a person in his or her professional role. Specifically, teacher development is the professional growth a teacher achieves due to gaining increased experience and examining his or her teaching systematically. Professional development includes different types of events or activities by which the teachers take steps through their growth. Since, English language teachers in Malaysian schools, where English is known as a second language, are the professionals who have to fulfill the learners’ high expectations; they need to constantly develop professionally. However, not many school systems survey the teachers’ professional development needs and interests. This study surveys the PD perception of all English Language teachers of all schools in Melaka,Malaysia. With the precise support of the language department of Jabatan Pelajaran, 1035 valid responses were collected from the total of 1098 English language teachers of schools in Melaka. The teachers’ overall perception of Need for Professional Development (NPD) was reported to be about 99% in some levels out of which 48.5% indicated it to be high or very high. Maintaining language skills, assessing students, and using cooperative learning were respectively the first, second and third instructional skills in item two for which teachers indicated high or very high levels of NPD. Testing the probable relationships between NPD and demographic variables of the teachers through Chi-Square, it was statistically verified (with 0.95confidence level) that age, ethnicity, years of experience, educational level, and teaching school level have the relationship significantly while it was not true about the gender. Item three surveyed the levels of English Language teachers’ interests in 10 types of PD activities. Collaborating with other teachers, participating in in-school, principal or district sponsored workshops, and traveling or studying abroad were reported by the greatest proportion of teachers for whom they were of very high or high level of interest. With regard to their PD experiences, about a third of the participants indicated that they had attended some PD activities through which higher levels of helpfulness were indicated. Additionally, merely about 42% were asked for the feedback after each activity. Finally, they reported that their major lack for participating in any PD activity was to receive release time rather than merely the financial support The findings of this study could comprehensively describe the professional development situation of all English language teachers in Melaka State as well as an overall status of Malaysian English language teachers in both primary and secondary schools. It also provides the local educational system with a revival mechanism on the basis of information obtained from ESL teachers along with their professional development needs, interests, experiences, and demographics. This also confirmed that considering the teachers perceptions leads the administrators to design a more supportive PD opportunity.